LINGKUNGAN KERJA DAN KEPEMIMPINAN KEPALA SEKOLAH MEMODERASI PENGARUH KOMPETENSI GURU TERHADAP KINERJA GURU (Studi Pada Madrasah Aliyah Swasta di Kecamatan Sayung Kabupaten Demak) - 11.52.02.0157, Farikhin (Jurnal Mahasiswa Pasca Sarjana, 2013)
This research is explanatory (explanatory research), the research aimed to clarify the causal relationship between the study variables and test hypotheses about the influence of teacher competence on Teacher Performance, Work Environment influence on teacher performance, the influence of the principals leadership on teacher performance, the role of Work environment on the relationship of Teachersâ Competence and Performance, the role of the Principal Leadership on relationship of Teachersâ Competence and Teacher Performance in Madrasah Aliyah Private Sub Sayung Demak.Respondents in this study were all teachers of Madrasah Aliyah Private Sub Sayung Demak regency were 169 respondents from 8 Madrasah Aliyah. This study uses sampling with purposive sampling method, the sample taken based on the criteria that have been certified, a total of 55 respondents. To test the hypothesis, the empirical model of moderation quasi linear regression with the independent variables they are Teacher Competence, Work Environment, Principal Leadership, Relationship of Teacher Competence and Work Environment, Relationship of Principal Leadership and Teacher Competence and dependent variable is Teacher Performance.From the test results, the mean value of the regression variables and interactions for moderating variables obtained coefficient of determination (adjusted R square ) of 0.705, meaning that 70.5 % change in the dependent variable can be explained by the interaction of the independent variables. Results of data analysis showed that there were no significant effects between Teacher Competence and teachersâ Performance, there is a significant but negative influence between work Environmental with teachers Performance, there is a positive and significant effect between the Principal Leadership on Teacher performance, work environment and significantly weaken moderate relationship between teacher competence with teacher performance, and reinforce moderate the Principal Leadership of relationship between teacher competencies on teacher performance. Keywords : Teacher Competence, Work Environment, Principal Leadership and Teacher Performance Â